2021
DOI: 10.34172/hpp.2021.61
|View full text |Cite
|
Sign up to set email alerts
|

He hurts her womb: Physical-sexual violence and pregnancy complications among women in Afghanistan

Abstract: Background: Though some studies show the association between intimate partner violence and pregnancy complications in developed countries, the association remains understudied in less developed and low-income settings. This study examines the association of physical and sexual violence with pregnancy complications among women in Afghanistan. Methods: This study used the data from the 2015 Afghanistan Demographic and Health Survey (AfDHS). The analysis included 7229 women aged between 15 and 49 and used logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Beating wife not justified index: Beating wife not justified was a summative index composed of the following five items representing women’s perception about violence perpetrated by their husbands/partners against them [ 27 ]: a) “Beating justified if wife goes out without telling husband”, b) “Beating justified if wife neglects the children”, c) “Beating justified if wife argues with husband”, d) “Beating justified if wife refuses to have sex with husband”, and e) “Beating justified if wife burns the food”. The response “no” to all these items was coded 0, and the response “yes” was coded 1, while the response “don’t know” was coded missing.…”
Section: Methodsmentioning
confidence: 99%
“…Beating wife not justified index: Beating wife not justified was a summative index composed of the following five items representing women’s perception about violence perpetrated by their husbands/partners against them [ 27 ]: a) “Beating justified if wife goes out without telling husband”, b) “Beating justified if wife neglects the children”, c) “Beating justified if wife argues with husband”, d) “Beating justified if wife refuses to have sex with husband”, and e) “Beating justified if wife burns the food”. The response “no” to all these items was coded 0, and the response “yes” was coded 1, while the response “don’t know” was coded missing.…”
Section: Methodsmentioning
confidence: 99%
“…Existing literature has identified exposure to different types of IPV as a significant risk factor for singular pregnancy complications during the prenatal period (Audi et al, 2012;Khaironisak et al, 2017). For example, Ferdos and colleagues (2017) found that physical IPV and sexual IPV sustained during pregnancy were each associated with a 5-fold increase in the risk of pregnancy complications, whereas Rahman et al (2021) found that lifetime exposure to physical and sexual IPV doubled the risk of pregnancy complications. Using bivariate analyses, Avanigadda and Kulasekaran (2021) found that physical, sexual, and psychological IPV were significantly related to experiencing more pregnancy complications; when accounting for factors like marital control, however, only physical and sexual IPV remained significant.…”
mentioning
confidence: 99%